Research progress on C-coated Ti composite powders used for preparing high-performance Ti matrix composites - LI Shao-fu; YANG Ya-feng (Fenmo yejin jishu)
The morphology and distribution of reinforcements in the titanium matrix composites (TMCs) are crucial in determining the material performances. Due to the uncontrollable morphology and inhomogeneous distribution of the reinforcements in the current TMCs, a series of C-coated Ti composite powders were developed by fluidization technology. By designing the structure and composition of C-coatings, the different morphology combinations and the intragranular/interface reinforcements were both achieved, which significantly improved the mechanical properties of TMCs. Furthermore, the composite powders were also extended to the 3D printing of TMCs, which solved the bottleneck issue of lacking the high-quality composite powders. The research results and work progress of the C-coated Ti composite powders in the preparation of high-performance TMCs were summarized and reviewed, providing the new insight and technical route for the design and control of reinforcements in TMCs.